PENGARUH TERPAAN AKUN INSTAGRAM @zerowaste.id_official DALAM MENGAMPANYEKAN GAYA HIDUP NOL SAMPAH TERHADAP SIKAP RAMAH LINGKUNGAN FOLLOWERS - Shindy Jafriyanti; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In this digital age, people always use social media to build a community of users to interact and exchange ideas. Along with the rapid progress of the times, social media, especially Instagram, can be used as a persuasive medium such as campaigning. The Zero Waste Indonesia Community is one of the environmental social movements that actively campaign for the environment regarding an online-based zero waste lifestyle using the @zerowaste.id_official account as a campaigning medium which aims to invite its followers to believe in the idealism of an environmentally friendly lifestyle, for socio-environmental change in the future. This study aims to determine how much influence Instagram account exposure has in campaigning for a zero waste lifestyle on followers' eco-friendly attitudes using quantitative research methods. The number of respondents in this study amounted to 398 respondents. To analyze the data, the researcher used the SPSS for Windows version 25 application. Based on the results of simple linear regression analysis, the results of the coefficient value in this study are Y = 23.016 + 0.939 X. Where, Ho is rejected and Ha is accepted with a significance level of 0.000. The coefficient of determination or R square in this study is 40.7%, which shows that the influence of the @ zerowaste.id_official Instagram account exposure in campaigning for a zero waste lifestyle on followers' environmental friendly attitudes is in the moderate category.                                                 Keywords: Exposure, Instagram, Campaign,  Environmental